Anterior subluxation of the cervical spine: hyperflexion sprain. - Green, J D; Harle, T S; Harris, J H (American Journal of Neuroradiology, 1981)
Anterior subluxation (hyperflexion sprain) is localized, purely ligamentous disruption of the cervical spine caused by a limited flexion force. When associated with a simple wedge fraction, also a flexion injury, anterior subluxation may be the more significant lesion. Radiographically, anterior subluxation is characterised by (1) a localized kyphotic angulation at the level of injury; (2) anterior rotation, or displacement, of the subluxed vertebra; (3) anterior narrowing and posterior widening of the disc space; (4) widening of the space between the subluxed vertebral body and the subjacent articular masses; (5) displacement of the inferior articulating facets of the subluxed vertebra with respect to their contiguous subjacent facets; and (6) widening of the interspinous space ("fanning"). The localized kyphotic angulation at the level of ligamentous disruption distinguishes pathologic anterior subluxation from diffuse "reversal of the normal cervical lordosis"; produced by voluntary positioning or muscle spasm. Anterior subluxation is clinically significant because of the approximate 20% incidence of delayed instability due to impaired ligamentous healing.